Is palliative care a utopia for older patients with organ failure, dementia or frailty? A qualitative study through the prism of emergency department admission - Delphine Bourmorck; Benoit Pétré; Marie de Saint-Hubert; Isabelle De Brauwer (BMC, 2024)
Abstract Background Nearly three out of four older people will use the emergency department (ED) during their last year of life. However, most of them do not benefit from palliative care. Providing palliative care is a real challenge for ED clinicians who are trained in acute, life-saving medicine. Our aim is to understand the ED's role in providing palliative care for this population. Methods We designed a qualitative study based on 1) interviews - conducted with older patients (≥ 75 years) with a palliative profile and their informal caregivers - and 2) focus groups - conducted with ED and primary care nurses and physicians. Palliative profiles were defined by the Supportive and Palliative Indicators tool (SPICT). Qualitative data was collected in French-speaking Belgium between July 2021 and July 2022. We used a constant inductive and comparative analysis. Results Five older patients with a palliative profile, four informal caregivers, 55 primary and ED caregivers participated in this study. A priori, the participants did not perceive any role for the ED in palliative care. In fact, there is widespread discomfort with caring for older patients and providing palliative care. This is explained by multiple areas of tensions. Palliative care is an approach fraught with pitfalls, i.e.: knowledge and know-how gaps, their implementation depends on patients'(co)morbidity profile and professional values, experiences and type of practice. In ED, there are constant tensions between emergency and palliative care requirements, i.e.: performance, clockwork and needs for standardised procedures versus relational care, time and diversity of palliative care projects. However, even though the ED's role in palliative care is not recognised at first sight, we highlighted four roles assumed by ED caregivers: 1) Investigator, 2) Objectifier, 3) Palliative care provider, and 4) Decision-maker on the intensity of care. A common perception among participants was that ED caregivers can assist in the early identification of patients with a palliative profile. Conclusions Currently, there is widespread discomfort regarding ED caregivers caring for older patients and providing palliative care. Nonetheless, ED caregivers play four roles in palliative care for older patients. In the future, ED caregivers might also perform the role of early identifier.